2017
DOI: 10.3329/sja.v15i1.33162
|View full text |Cite
|
Sign up to set email alerts
|

DNA fingerprinting and genetic diversities in some Bangladeshi aus rice (Oryza sativa L.) genotypes

Abstract: The allelic diversity and relationship among 120 Aus rice landraces were determined through DNA fingerprinting using microsatellite (SSR) markers. A total of 85 SSR markers were used to characterize and discriminate all tested Aus rice genotypes, 45 of which were polymorphic for different chromosome numbers. The number of alleles per locus varied from 6 alleles (RM484 and RM541) to 30 alleles (RM519) with an average of 13 alleles per locus. The polymorphic information content (PIC) values varied ranged from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Very few studies, however, have investigated the genetic diversity of Aus rice in Bangladesh [ 6 8 ]. While more comprehensive research into genetic variability, as well as the population configuration, of Aus varieties would inform germplasm utilization for rice breeding, research into morphological and agronomic variation will also be needed for any future breeding program.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies, however, have investigated the genetic diversity of Aus rice in Bangladesh [ 6 8 ]. While more comprehensive research into genetic variability, as well as the population configuration, of Aus varieties would inform germplasm utilization for rice breeding, research into morphological and agronomic variation will also be needed for any future breeding program.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies regarding the characterisation of Bangladeshi Aus rice, and some landraces have been reported thus far using SSR markers (Islam et al 2017(Islam et al , 2018. A majority of studies are either only limited to the molecular marker or to the biochemical or morphological markers for the characterisation.…”
mentioning
confidence: 99%
“…In another study, Siddique et al (2016) found a PIC value of 0.90 among 96 Bangladeshi Aman rice employing 8 SSR markers. Islam et al (2017) studied genetic diversity in 120 Aus rice genotypes of Bangladesh and observed a PIC value of 0.8217. Other studies conducted using SSR markers reveled a polymorphism information content of 0.697 (Rashid et al, 2018), 0.6533 (Shakil et al, 2015), 0.36 (Syed et al, 2019) and 0.51 (Verma et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(2016) found a PIC value of 0.90 among 96 Bangladeshi Aman rice employing 8 SSR markers. Islam et al. (2017) studied genetic diversity in 120 Aus rice genotypes of Bangladesh and observed a PIC value of 0.8217.…”
Section: Discussionmentioning
confidence: 99%